Asymmetric localization of the cell division machinery during Bacillus subtilis sporulation - Khanna, Kanika; Lopez-Garrido, Javier; Sugie, Joseph; Pogliano, Kit; Villa, Elizabeth (eLife, 2021)
The Gram-positive bacterium Bacillus subtilis can divide via two modes. During vegetative growth, the division septum is formed at the midcell to produce two equal daughter cells. However, during sporulation, the division septum is formed closer to one pole to yield a smaller forespore and a larger mother cell. Using cryo-electron tomography, genetics and fluorescence microscopy, we found that the organization of the division machinery is different in the two septa. While FtsAZ filaments, the major orchestrators of bacterial cell division, are present uniformly around the leading edge of the invaginating vegetative septa, they are only present on the mother cell side of the invaginating sporulation septa. We provide evidence suggesting that the different distribution and number of FtsAZ filaments impact septal thickness, causing vegetative septa to be thicker than sporulation septa already during constriction. Finally, we show that a sporulation-specific protein, SpoIIE, regulates asymmetric divisome localization and septal thickness during sporulation.
Keywords: cell division; FtsZ; FtsA; SpoIIE; peptidoglycan; cryo-electron tomography